Ni-Sr(V,Ti,Ni)O3 electrodes for reversible solid electrolyte cells - Costa , Bernardo Filipe Serôdio (2020)
The main objective of this work was to assess the possibility of the enhancement of the electrocatalytic activity of Sr(Ti,V)O3-δ fuel electrode components for high-temperature solid electrolyte cells by introducing Ni into the B-sublattice of the perovskite structure with in-situ nanostructuring under operation conditions by exsolution. The work was motivated by the drawbacks of commonly used cermet Ni-YSZ cermet anodes such as long-term microstructural degradation and intolerance to redox changes, sulfur poisoning and carbon deposition. Strontium titanate-vanadates were considered as suitable ceramic components stable under fuel electrode operation conditions and with prospects for sulfur and carbon deposition tolerance, while nano-dispersed Ni was expected to enhance the electrocatalytic activity while avoiding the disadvantages of Ni-YSZ cermets. High-energy mechanochemical route in combination with thermal treatments under controlled reducing atmosphere were employed for the preparation of selected materials with a nominal composition Sr1-xTi1-y-zVyNizO3 (x = 0-0.04, y = 0.2-0.4, z = 0.02-0.12). Detailed analysis of the phase formation in this system revealed that comparatively high thermal treatment temperature (1200°C), required to eliminate the undesired insulating Sr3(VO4)2 intermediate phase in the course of synthesis of Sr(Ti,V)O3 perovskites, results in a segregation of Ni in the form of poorly dispersed submicron metallic particles. Prepared Sr1-x(Ti,V)O3-δ-Ni ceramic materials exhibited a moderate thermal expansion coefficients compatible with that of YSZ solid electrolyte. The electrical conductivity was found to increase with increasing vanadium content in the perovskite phase, while the nominal A-site deficiency had an opposite effect. The electrochemical impedance spectroscopy studies revealed a rather poor activity of Sr1-x(Ti,V)O3-δ-Ni porous electrodes for hydrogen oxidation reaction. This was ascribed to insufficient intrinsic electrocatalytic activity of Sr1-x(Ti,V)O3 perovskites, low expected ionic conduction in these phases, and segregation of Ni particles in the course of synthesis. It was demonstrated that the electrochemical performance of these electrodes can be substantially improved by the infiltrations of gadolinia-doped ceria as oxygen-ion conducting component and small extra amounts of well-dispersed Ni as an electrocatalyst